TRANSFORMASI LEMBAGA PENDIDIKAN ISLAM: MADRASAH DINIYAH AL-IKHLAS DI BUNGBULANG GARUT (1997-2021) - Yuserizal Bustami; Egi Prayogi Pangeresa; Andri Nurjaman; Kesi Afrilia (Balai Diklat Keagamaan Medan, 2023)
A knowledge of religion which is classified as very little, is presented at the elementary school level regarding knowledge of the Islamic Religion which makes the nation's generation not have a strong foundation. Religious learning which is expected to be able to instill Islamic knowledge becomes hampered, due to the limited time regulated by class hours. So in 1997, the Al-Ikhlas Madrasah Diniyah was founded by K.H. Ahmad Husaeni who was able to complete the limited time for teaching religious knowledge at the elementary school level. Besides that, the function of teaching at the Madrasah Diniyah level is to realize the teachings of Islam by a Muslim as the demands and expectations of parents for their children. This research seeks to find out and examine the transformation of Madrasah Diniyah Al-Iklhlas which was originally salafi to khalafi and scores of various achievements resulting from its learning. This article uses historical research methods consisting of heuristics, criticism, interpretation, and historiography. The results of the study show that Madrasah Diniyah Al-Ikhlas has significance in preserving the continuity of Islamic education, namely, an institution for transforming religious knowledge, media for preserving religious knowledge, a vehicle for planting as well as the formation of akhlakul karimah, and to complement Islamic religious education in elementary schools.